Experimental and techno-economic analysis of transcritical CO2 heat pump water heater with fin-and-tube and microchannel heat exchanger. (25th November 2021) - Wang, Yikai; Zong, Shuo; Song, Yulong; Cao, Feng; He, Yaling; Gao, Qiang
Highlights: The CO2 heat pump with fin-and-tube and microchannel heat exchangers is compared. Coefficient of performance is raised by 16.32–22.62% with microchannel heat exchanger. The frosting performance of heat pump with two different heat exchangers is discussed. The primary energy consumption and enviroeconomic cost are reduced with microchannel. The life cycle cost and sensitivity analysis with unit electricity price is presented. Abstract: Previously, the conventional fin-and-tube heat exchanger is usually chosen as the evaporator in the air source heat pump. Recently, with the higher heat transfer efficiency, the microchannel heat exchanger is increasingly recognized. Nevertheless, information available in the contrastive analysis of the two heat exchanger types is scarce. Therefore, the effect of the mentioned evaporator type on the air source transcritical CO2 heat pump was experimentally studied in this paper. Then, with the detailed techno-economic analysis methods, the heat pump with different heat exchangers is evaluated from multiple perspectives. Results showed the heating capacity and coefficient of performance of the microchannel system were increased by 16.5%-37.3% and 16.3%–22.6%, compared with the baseline fin-and-tube system. However, the attenuation degree of heating capacity was more obvious in the fin-and-tube system under the frosting condition. The primary energy consumption, CO2 emission and corresponding cost of microchannel system are declined by 6.28 tce, 14.4 tons and 77.6 dollars for the comparison with the fin-and-tube system. The maximum values are all presented by direct electric heater whereas the minimum life cycle cost is achieved by coal-fired boiler. The life cycle cost and sensitivity analysis with unit electricity price are also conducted in the economic analysis.